1996
DOI: 10.1177/030098589603300612
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Cystic Disease of the Liver, Pancreas, and Kidney in a Nubian Goat (Capra hircus)

Abstract: A congenital cystic disease of the liver, pancreas, and kidney was diagnosed in a 3-week-old female Nubian goat (Cupru hircus). Gross and histologic features were similar to autosomal recessive polycystic kidney disease in humans and to previous reports of juvenile polycystic disorders in several animal species. Grossly, the lesions were confined to the liver and pancreas. The liver was severely enlarged and contained multiple fluid-filled cysts of various sizes. There was tortuous ectasia of the extrahepatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 7 publications
0
14
1
Order By: Relevance
“…The literature contains reports of polycystic disorders in African gazelles, cats, dogs, mice, pigs, and, most recently, a 3.5-week-old Nubian goat. 4,6,8,[10][11][12][13][14] The present case has a clinical and pathologic presentation similar to 1 case described previously in a Nubian goat kid, but, in contrast, there were both gross and histologic lesions in the kidney and liver and the pancreas was unaffected.…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…The literature contains reports of polycystic disorders in African gazelles, cats, dogs, mice, pigs, and, most recently, a 3.5-week-old Nubian goat. 4,6,8,[10][11][12][13][14] The present case has a clinical and pathologic presentation similar to 1 case described previously in a Nubian goat kid, but, in contrast, there were both gross and histologic lesions in the kidney and liver and the pancreas was unaffected.…”
mentioning
confidence: 52%
“…10,11,14 Cystic disease was suspected in four juvenile Nubian goats over a 5-year period in the herd with the documented case, but necropsy examinations were not performed to confirm this suspicion. 8 The goat described in this case report was from a primiparous doe and was born with a twin that died from unknown causes at birth.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…As in humans, most cystic hepatic disorders are regarded as a congenital malformation (Krotec et al, 1996;McAloose et al, 1998;Straub et al, 2003) and cystic formations can also be present in the kidneys and pancreas (McKenna and Carpenter, 1980;Krotec et al, 1996;Bosje et al, 1998). In most cases liver cysts do not communicate with the intrahepatic biliary duct system and are filled with water and electrolytes without containing bile acid and bilirubin (Van den Ingh and Rothuizen, 1985).…”
mentioning
confidence: 99%
“…The autosomal recessive form is rare, often diagnosed in early infancy by massive nephromegaly, and is rapidly progressive. 17 Syndromes resembling both the recessive and dominant forms of human PKD have been recognized in animals including cats, 1,2 where Persian cats appear disproportionately affected, 8 dogs, 9,15 mice, 13 pigs, raccoons, 5 and ruminants such as cattle, 14 goats, 7,10 sheep, 3 and springbok (Antidorcas marsupialis). 6 To the authors' knowledge, PKD has not been reported in any member of the family Cervidae.…”
mentioning
confidence: 99%